The diagnostic value of fine needle aspiration biopsy in bilateral swellings of the parotid. - Musayev, J. S.; Hasanov, A. B.; Karimova, I. I. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Fine needle aspiration biopsy (FNAB) is a frequently used method in the diagnosis of masses and it has been employed in pre-operative diagnosis of salivary gland lesions for many years. There are many publications in the literature on diagnostic value of FNA in salivary gland masses. However, studies involving FNA results of multiple lesions of salivary glands are rare. Objective. The purpose of present study is to determine the diagnostic value of FNAB in the bilateral, especially in the diffuse, swellings of the parotid gland and detection of pitfalls and their consequences. Methods. A total of 19 cases of bilateral swelling of parotid gland were included in this study. Demographic and clinical features of patients, results of FNAB and postoperative histopathological examination in some cases were analyzed retrospectively. Results. Eleven (57,89%) of patients were female, 8 (42,11%) were male. The age range of patients was 33-74 and mean age was 49,05. Benign non-neoplastic disease in 15 (78,95%), and benign neoplastic disease in 4 (21,05) of 19 cases were detected with FNAB. Conclusion. FNAB is the accessible, inexpensive and reliable method in the diagnosis and selection of the treatment tactics of the bilateral parotid swellings. Biopsies from both sides separately are advisable to prevent diagnostic errors in the bilateral parotid swellings, especially in the cases of Warthin tumour.